Pariwisata Berbasis Kearifan Lokal di Desa Wisata Ubud: Antara Komersialisasi dan Pelestarian Budaya - Wirawan, Putu Eka (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to examine the dynamics between the preservation of local wisdom and the commercialization of culture within the development of tourism in Ubud Tourism Village, Bali. Using a descriptive qualitative approach, data were collected through participatory observation and in-depth interviews with community leaders, artists, and local tourism actors. The findings reveal that elements of local wisdom such as Tri Hita Karana, the banjar system, as well as traditional rituals and performing arts, remain integral to the community’s way of life. However, tourism has also led to cultural commodification, where traditional practices and symbols are adapted and repurposed for tourist consumption, often altering their original meanings. The local community responds to these challenges through cultural negotiation strategies and active participation in community-based tourism management. This study is supported by the theories of cultural sustainability, cultural commodification, cultural negotiation, and community participation. It concludes that tourism in Ubud exists within a dynamic spectrum between cultural preservation and commercialization, and that cultural sustainability can be achieved through empowering local participation and maintaining community control over cultural narratives. Keywords: local wisdom, commercialization, cultural preservation